Financial Crisis and the South African Agricultural Sector: A Computable General Equilibrium (CGE) Analysis - Fadeyi, Oluwatoba A.; Sedibe, Moosa M.; Van der Westhuizen, Carlu; Igene, Lucky (African Journal of Business and Economic Research, 2019)
This study examines the impact of financial crisis as a shock on agricultural sector of the South African economy. Agriculture is regarded as a critical source of foreign exchange, employment and poverty alleviation in South Africa. Using a computable general equilibrium model of the South African economy based on the theory of ORANI-G framework, it was discovered that the impact of the financial crisis on agricultural sector was harmful to the economy. Job losses were recorded in the sector as well as decline in household demand. The financial crisis was also found to be harsh on domestic prices and general household consumption levels. The findings have far-reaching implications for research and practice. The results provide evidence of the vulnerability of the South African agricultural sector to any financial shocks.
Published Article
Keywords: CGE Analysis; Financial Crisis; Agriculture; Employment; South Africa